Identification of Specificity Determinants and Generation of Alleles with Novel Specificity at the het-c Heterokaryon Incompatibility Locus of Neurospora crassa - Wu, Jennifer (American Society for Microbiology, 2001)
The capacity for nonself recognition is a ubiquitous and essential aspect of biology. In filamentous fungi, nonself recognition during vegetative growth is believed to be mediated by genetic differences at heterokaryon incompatibility (het) loci. Filamentous fungi are capable of undergoing hyphal fusion to form mycelial networks and with other individuals to form vegetative heterokaryons, in which genetically distinct nuclei occupy a common cytoplasm. In Neurospora crassa, 11 het loci have been identified that affect the viability of such vegetative heterokaryons. The het-c locus has at least three mutually incompatible alleles, termed het-c(OR), het-c(PA), and het-c(GR). Hyphal fusion between strains that are of alternative het-c specificity results in vegetative heterokaryons that are aconidial and which show growth inhibition and hyphal compartmentation and death. A 34- to 48-amino-acid variable domain, which is dissimilar in HET-C(OR), HET-C(PA), and HET-C(GR), confers allelic specificity. To assess requirements for allelic specificity, we constructed chimeras between the het-c variable domain from 24 different isolates that displayed amino acid and insertion or deletion variations and determined their het-c specificity by introduction into N. crassa. We also constructed a number of artificial alleles that contained novel het-c specificity domains. By this method, we identified four additional and novel het-c specificities. Our results indicate that amino acid and length variations within the insertion or deletion motif are the primary determinants for conferring het-c allelic specificity. These results provide a molecular model for nonself recognition in multicellular eucaryotes.